Performance of circular patch microstrip antenna for adaptive modulation and coding applications - Hiba A. Alsawaf; Bushra Muhammed Ahmad (Bulletin of Electrical Engineering and Informatics, 2022)
The thickness of the substrate is one factor influencing antenna performance. In this paper, the circular patch antenna was designed using rogers RT5880 with dielectric constant of 2.20, loss kept 0.0009 and FR-epoxy with dielectric constant of 4.4, loss kept 0.02. The thickness of the substrate was varied to see how it affected antenna performance, such as return loss. The thickness of the checked substrate is 1.58 mm, which is the standard thickness for rogers RT5880 as well as 2.08 mm, 2.58 mm and 2.85 mm. The simulation work is carried out by ANSYS HFSS software. In this paper, the thicknesses of different substrates are checked while other parameters stay constant and the circular patch radius of the antennas is optimized to achieve a resonant frequency of 3.5 GHz based on the thickness of the above-mentioned substrates used. Return loss, VSWR, gain and half power beam width were found, and the results showed that with the increase in the thickness of the substrate, the gain increases and the value of half power beam width (HPBW) and better results were obtained in the case of RTduroid 5880 and for thicknesses h=2.85 mm